On the effect of poly(3-hexylthiophene) regioregularity on inkjet printed organic solar cells - Hoth, Claudia N.; Choulis, Stelios A.; Schilinsky, Pavel; Brabec, Christoph J. (My University, 2009)
We investigate the impact of P3HT regioregularity on the performance of bulk heterojunction solar cells with inkjet printed P3HT:PCBM layers. Three polythiophenes with different regioregularities ranging from 93% up to 98% are inkjet printed from two different formulations at room temperature. It is found that the high RR-P3HT (98%) is not suitable for inkjet printing at room temperature. The fast formation of aggregates shortens the shelf life of the ink and thus, results in low reliability of the printing process, in the formation of inhomogeneous and very rough films with surface roughnesses up to 70 nm, and in a strongly reduced device performance. This phenomenon is not observed for solar cells processed via the doctor blading technique. Nevertheless, inkjet printing of 96% RR-P3HT:PCBM oDCB/mesitylene solutions at room temperature resulted in solar cells with 3.5% efficiency, while doctor blading of 98% RR-P3HT:PCBM oDCB/mesitylene solutions resulted in efficiencies as high as 4.4%
Keywords: Ink-jet printing; Solar cells; Agglomeration; Cell membranes; Heterojunctions; Ink; Photovoltaic cells